Optimalisasi Keuntungan Roti Panggang Menggunakan Pemrograman Linear Metode Simpleks (International Forum of Researchers and Lecturers, 2023)
Toast is a common and popular food all over the world. Toast is generally made from slices of bread that are toasted until golden brown on the outside and soft on the inside. The basic bread used varies, from white bread to whole wheat bread, and can be cut in various shapes. The toasting process is a key stage in making toast, where the pieces of bread are toasted until they reach the desired doneness. Fillings are an important element in toast, with various options such as butter, jam, cheese, chocolate and nuts. Bread ingredients such as bread, butter, canned milk, etc. are a problem. If one of these ingredients is not met then production in the bakery business will be hampered. Therefore, to find out what variables hinder optimal value in the bakery business, mathematical modeling can be created using the simplex linear method program.